Experimental Investigation of Phase Equilibria in the ZrO2–TiO2–MgO System. Issue 5 (6th September 2018) - Saenko, Ivan; Tsukrenko, Viktoria; Ilatovskaia, Mariia; Pavlyuchkov, Dmytro; Savinykh, Galina; Fabrichnaya, Olga
Abstract : Phase equilibria in the ZrO2 –TiO2 –MgO system are studied experimentally using X‐ray diffraction (XRD), scanning electron microscopy combined with dispersive X‐ray spectrometry (SEM/EDX), and differential thermal analysis (DTA). Based on the obtained experimental data, isothermal sections of the ZrO2 –TiO2 –MgO system at temperatures 1530, 1680, and 1880 K are established. Wide extension of stability of Zr1‐ x Mgx O2‐ x phase with fluorite structure (C ZrO2 ) into ternary system is revealed. Very limited solubility of MgO is found in β‐(Zr x Ti1‐ x )2 O4 and tetragonal (Zr1‐ x Ti x )O2 phase (T ZrO2 ), while more substantial solubility of ZrO2 is found in the intermediate compounds of the TiO2 –MgO system (Mg2 TiO4, MgTiO3, and MgTi2 O5 ). Low temperature ternary compound similar to δ‐phase Y4 Zr3 O12 is revealed at 1530 K. Differential thermal analysis indicated that this δ‐phase is stable up to 1664 K. Temperatures and compositions of three eutectic reactions are experimentally measured by DTA and ex situ analysis of the sample microstructures after melting using SEM/EDX. Abstract : New experimental study of the ZrO2 –TiO2 –MgO system is performed. Phase relations are investigated from 1530 to 1880 K. A new low temperature ternary compound similar to δ‐Y4 Zr3 O12 is revealed at 1530 K stable up to 1664 K. Solid state phase reactions and melting are investigated by DTA up to 1973–K followed by microstructure analysis using SEM/EDX.